Compact and ordered cadmium selenide quantum well film and method for preparing electroluminescent diode
Through the preparation method of dense and ordered cadmium selenide quantum well film, the problems of low efficiency of cadmium selenide quantum well light emitting diodes, disordered materials and insufficient stability are solved, and the electrogenesis of high external quantum efficiency and stability is achieved Light emitting diodes, suitable for commercial production.
Patent Information
- Application Number
- CN202411672866.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The efficiency of existing cadmium selenide quantum well light emitting diodes is lower than that of traditional quantum dot light emitting diodes, mainly due to the uncontrollable high excoupling factor of quantum wells, disordered material, limitations of spin coating process, interface defects, insufficient stability and durability And the issues of economy and scale of production.
By designing a densely ordered method for preparing a cadmium selenide quantum well film, including synthesizing the core and core-shell structure of the cadmium selenide quantum well, and arranging the quantum wells in an orderly manner, forming a high-performance electroluminescent diode.
It has achieved high external quantum efficiency and good stability, with an efficiency of up to 25%, and has good operating life and economy, which is suitable for large-scale production.
Smart Images

Figure CN119486549A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nanotechnology and luminescent display, and specifically relates to a preparation method of a cadmium selenide quantum well ordered dense film and an electroluminescent diode thereof, and belongs to the field of semiconductor luminescence, display and nanotechnology. Background Art
[0002] Colloidal quantum wells refer to colloidal semiconductor nanosheets with one-dimensional strong quantum confinement effects. Their surfaces are linked to organic ligands and exhibit monodisperse distribution characteristics. They have excellent optical properties, such as extremely narrow spectral emission, high fluorescence quantum yield, and excellent light-output coupling performance. They have broad application and development prospects in new light-emitting, display, detection and other fields.
[0003] The study of colloidal quantum wells originated in the 1990s. With the development of nanotechnology, researchers discovered the potential application of these quantum wells in optoelectronic devices. In particular, in terms of photoelectric conversion and optical signal processing, colloidal quantum wells have become a research hotspot due to their superior optical properties and simple synthesis methods. After entering the 21st century, with the in-depth study of their applications in light-emitting diodes, solar cells, and lasers, the relevant technologies have gradually matured, and market demand has also increased.
[0004] Cadmium chalcogenide materials (such as CdSe and CdS) have good optical and electronic properties, such as high light absorption coefficient, large exciton binding energy and excellent luminescence properties. These materials can produce strong fluorescence in the visible light region, and their size and shape can be precisely controlled by synthetic methods to achieve the regulation of optical properties. In addition, cadmium chalcogenide materials exhibit good carrier mobility in semiconductor applications, which makes them have broad application prospects in devices such as light-emitting diodes and photodetectors. CdSe quantum wells, as one of the important colloidal quantum well materials, have good optoelectronic properties and easy synthesis, which makes them highly competitive in display technology and sensors. In addition, the surface modification technology of cadmium chalcogenide materials also provides new ideas for improving their stability and biocompatibility, expanding their scope of application.
[0005] In recent years, light-emitting diode (LED) technology based on colloidal quantum wells has developed rapidly. These devices exhibit excellent luminous efficiency and color purity and are widely used in display technology and lighting. However, current technology still faces some challenges, such as insufficient densification. The arrangement and density of current colloidal quantum wells in devices are often insufficient, which leads to a decrease in photoluminescence efficiency. Low density may lead to light propagation loss and non-radiative recombination, thus affecting the overall performance of the device. Second, the problem of material disorder. During the synthesis and processing of colloidal quantum wells, the crystal structure often becomes disordered. This disorder may lead to a decrease in carrier mobility, thereby affecting the current injection efficiency and light emission efficiency, resulting in unstable device performance. Third, the limitations of the spin coating process. Although spin coating is a commonly used process for preparing colloidal quantum well LEDs, it has certain limitations when it is prepared over a large area. The spin coating process makes it difficult to ensure the consistency and uniformity of the film, affecting the overall performance of the device. In addition, the spin coating process has high requirements for the substrate, which limits its application scenarios. Fourth, interface defects and recombination centers. In the quantum well structure, interface defects and inhomogeneities will form recombination centers, resulting in increased carrier recombination losses, which in turn affects the luminescence efficiency. These defects are often caused by improper material synthesis, surface modification or device construction. Fifth, stability and durability. The chemical stability and photostability of colloidal quantum wells are usually poor. Under long-term illumination or thermal stress, photodegradation or structural changes are prone to occur, resulting in attenuation of luminescence performance. This puts higher demands on the reliability of devices in practical applications. Sixth, economy and production scale. Although there are various synthesis methods for colloidal quantum wells, the cost of large-scale production is high and it is difficult to meet commercial needs. Finding low-cost and high-efficiency synthesis methods and optimizing production processes have become the key to promoting the commercialization of this technology. Therefore, research and improvement on these issues are particularly important. Summary of the invention
[0006] The efficiency of cadmium selenide quantum well light-emitting diodes lags behind that of traditional quantum dot light-emitting diodes. Due to the uncontrollable high external coupling factor of quantum wells, the present invention designs a method for synthesizing cadmium selenide quantum wells and preparing dense and ordered cadmium selenide quantum well electroluminescent diodes. A method for orderly arranging quantum wells is designed, which is conducive to the realization of high-performance light-emitting diodes and large-scale production. The unique ordered quantum wells significantly improve the light output coupling, thereby obtaining an electroluminescent diode with high external quantum efficiency and good stability.
[0007] The present invention is achieved through the following technical solutions:
[0008] A method for preparing a dense and ordered cadmium selenide quantum well film specifically comprises the following steps:
[0009] (1) dissolving sodium myristate and cadmium nitrate tetrahydrate in a first solvent respectively, mixing them after they are completely dissolved to form cadmium myristate, filtering, washing with the first solvent, and drying for later use;
[0010] (2) CdSe quantum well core: 0.2~1.6 mmol of cadmium tetradecanoate and 0.1~0.8 mmol of selenium powder are mixed with a solvent, heated to 140~200 degrees Celsius in an inert gas atmosphere, and cadmium acetate dihydrate is injected. The temperature is then raised to 200~260 degrees Celsius and kept warm for 5~20 minutes. 0.2~1 ml of oleic acid is injected, and the temperature is cooled. The quantum wells are washed with a mixed solution of n-hexane and ethanol, and redispersed with a second solvent to form a CdSe quantum well core solution.
[0011] (3) Core-shell structure cadmium selenide / cadmium zinc sulfur: quantum well: 0.1-0.3 mmol of anhydrous cadmium acetate, 0.3-0.9 mmol of anhydrous zinc acetate, 0.5-1.5 ml of oleic acid and 0.2-1 ml of 1-octadecene are added to the above cadmium selenide quantum well solution. The mixture is heated to 70-100 degrees Celsius under an inert gas atmosphere and kept warm for 0.2-1 hour. 0.2-1 ml of oleylamine is injected and the temperature is raised to 280-320 degrees Celsius. When the temperature reaches 120-180 degrees Celsius, octanethiol is injected. The mixture is kept warm at 280-320 degrees Celsius for 0.5-1.5 hours and then cooled.
[0012] (4) washing the cadmium selenide core-shell quantum wells with a mixed solution of a second solvent and the first solvent, and redispersing with a second solvent to form a core-shell structured cadmium selenide / cadmium zinc sulfur quantum well solution; the first solvent is methanol and ethanol, and the second solvent is n-octane, n-hexane or chloroform.
[0013] (5) preparing a colloidal cadmium selenide quantum well solution with a concentration of 10 to 50 mg / ml using the above solution;
[0014] (6) In a nitrogen atmosphere at a temperature of 10 to 30 degrees Celsius, add the colloidal cadmium selenide quantum well chloroform solution dropwise to the ethylene glycol solution until the multi-quantum wells cover the ethylene glycol liquid surface, and then add tri-n-octylamine at a volume ratio of 1% to 10% of the ethylene glycol solution;
[0015] (7) After standing for 1 to 15 minutes, a dense and ordered cadmium selenide quantum well film is obtained.
[0016] A dense and ordered cadmium selenide quantum well film and an electroluminescent diode preparation method thereof, the preparation steps are as follows:
[0017] (1) The hole injection material is printed on the transparent conductive substrate to form a hole injection layer with a thickness of 30 to 70 nanometers, which is then annealed at 80 to 140 degrees Celsius for 10 to 30 minutes. Subsequently, the hole transport material is printed on the hole injection layer to form a hole transport layer with a thickness of 30 to 70 nanometers, which is then annealed at 100 to 150 degrees Celsius for 10 to 30 minutes.
[0018] (2) transferring the dense and ordered quantum well film prepared above to the hole transport layer to form an ordered quantum well light-emitting layer with a thickness of 5 to 20 nanometers, and annealing at 40 to 90 degrees Celsius for 10 to 30 minutes;
[0019] (3) Spin-coat a 20-50 mg / ml zinc oxide or magnesium-doped zinc oxide ethanol solution on the quantum well layer to form an electron transport layer with a thickness of 30-60 nm, and anneal at 60-90 degrees Celsius for 10-30 minutes;
[0020] (4) The metal cathode material is deposited on the electron transport layer by vacuum evaporation to form an electrode with a thickness of 70 to 100 nanometers to obtain an electroluminescent diode.
[0021] Furthermore, the hole injection material is poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid); the hole transport layer material is poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)]. The transparent conductive substrate is indium-doped tin oxide; and the metal cathode material is aluminum.
[0022] The beneficial effects of the present invention are:
[0023] (1) Ordered quantum well film formation: Compared with the traditional spin coating method, the direction of the quantum well is more controllable and dense, which is conducive to controllable production.
[0024] (2) Ordered quantum wells can obtain high external coupling quantum wells. Controllable and ordered quantum well films can improve external coupling efficiency and reduce leakage current caused by film inhomogeneity.
[0025] (3) Ordered quantum well light-emitting diodes have low current efficiency and high external quantum efficiency (efficiency can reach 25%), good working stability, and long operating life, which meet the requirements of actual use conditions. Therefore, the technology of the present invention is an important breakthrough in the field of quantum well light-emitting and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is an electron microscope photograph of densely ordered cadmium selenide quantum wells.
[0027] Figure 2 This is a schematic diagram of an ordered quantum well.
[0028] Figure 3 1 is the external quantum efficiency curve of the electroluminescent diode of Examples 1-5.
[0029] Figure 4 1 is the external quantum efficiency curve of the electroluminescent diodes of Examples 6-10.
[0030] Figure 5 1 is the external quantum efficiency curve of the electroluminescent diodes of Examples 11-13. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] On the contrary, the present invention covers any substitution, modification, equivalent method and scheme made on the essence and scope of the present invention as defined by the claims. Further, in order to make the public have a better understanding of the present invention, some specific details are described in detail in the detailed description of the present invention below. Those skilled in the art can fully understand the present invention without the description of these details.
[0033] A method for preparing a dense and ordered cadmium selenide quantum well film comprises the following steps:
[0034] (1) dissolving sodium myristate and cadmium nitrate tetrahydrate in a first solvent respectively, mixing them after they are completely dissolved to form cadmium myristate, filtering, washing with the first solvent, and drying for later use;
[0035] (2) CdSe quantum well core: 0.2~1.6 mmol of cadmium tetradecanoate and 0.1~0.8 mmol of selenium powder are mixed with a solvent, heated to 140~200 degrees Celsius in an inert gas atmosphere, and cadmium acetate dihydrate is injected. The temperature is then raised to 200~260 degrees Celsius and kept warm for 5~20 minutes. 0.2~1 ml of oleic acid is injected, and the temperature is cooled. The quantum wells are washed with a mixed solution of n-hexane and ethanol, and redispersed with a second solvent to form a CdSe quantum well core solution.
[0036] (3) Core-shell structure cadmium selenide / cadmium zinc sulfur: quantum well: 0.1-0.3 mmol of anhydrous cadmium acetate, 0.3-0.9 mmol of anhydrous zinc acetate, 0.5-1.5 ml of oleic acid and 0.2-1 ml of 1-octadecene were added to the above cadmium selenide quantum well solution. The mixture was heated to 70-100 degrees Celsius under an inert gas atmosphere and kept warm for 0.2-1 hour. 0.2-1 ml of oleylamine was injected. Argon was switched and the temperature was raised to 280-320 degrees Celsius. When the temperature reached 120-180 degrees Celsius, octanethiol was injected. The mixture was kept warm at 280-320 degrees Celsius for 0.5-1.5 hours and then cooled.
[0037] (4) washing the cadmium selenide core-shell quantum wells with a mixed solution of a second solvent and the first solvent, and redispersing with the second solvent to form a core-shell structured cadmium selenide / cadmium zinc sulfur quantum well solution. The first solvent is methanol and ethanol, and the second solvent is n-octane, n-hexane or chloroform.
[0038] Prepare a solution concentration of 10-50 mg / ml of colloidal cadmium selenide / cadmium zinc sulfur quantum well solution;
[0039] (5) In a nitrogen atmosphere at a temperature of 10 to 30 degrees Celsius, add the cadmium selenide / cadmium zinc sulfur quantum well solution dropwise onto the ethylene glycol solution until the quantum wells cover the entire ethylene glycol liquid surface, and then add 1% to 10% of tri-n-octylamine by volume of the entire solution;
[0040] (6) After standing for 1 to 15 minutes, a dense and ordered cadmium selenide quantum well film is obtained.
[0041] Example 1
[0042] The method for preparing a dense and ordered cadmium selenide quantum well film comprises the following steps:
[0043] (1) dissolving sodium tetradecanoate and cadmium nitrate tetrahydrate in methanol solvent respectively, mixing them after they are completely dissolved to form cadmium tetradecanoate, filtering, washing with methanol solvent, and drying for later use;
[0044] (2) CdSe quantum well core: 0.8 mmol of cadmium tetradecanoate and 0.4 mmol of selenium powder were mixed with 30 ml of 1-octadecene solvent, heated to 140 °C in an inert gas atmosphere, injected with 20 mg / ml cadmium acetate dihydrate methanol solution, then heated to 200 °C and kept warm for 10 min, injected with 0.5 ml of oleic acid, cooled, washed with a mixed solution of n-hexane and ethanol, and redispersed with n-hexane solvent to form a CdSe quantum well core solution.
[0045] (3) Core-shell structure cadmium selenide / cadmium zinc sulfur quantum well: 0.1 mmol anhydrous cadmium acetate, 0.3 mmol anhydrous zinc acetate, 0.5 ml oleic acid, and 0.2 ml 1-octadecene were added to the above cadmium selenide quantum well core solution, and the mixture was heated to 70 degrees Celsius under an inert gas atmosphere and kept warm for 1 hour. 0.5 ml oleylamine was injected, and argon gas was switched. The temperature was raised to 280 degrees Celsius. When the temperature reached 160 degrees Celsius, 0.4 mmol octanethiol was injected. The temperature was kept warm at 280 degrees Celsius for 1 hour, and the mixture was cooled and redispersed using chloroform solvent to form a cadmium selenide / cadmium zinc sulfur quantum well solution.
[0046] (4) Prepare a 10 mg / ml colloidal cadmium selenide quantum well chloroform solution. In a nitrogen-protected environment at an ambient temperature of 25 degrees Celsius, drop 10 μl of the quantum well solution on 20 ml of ethylene glycol solution. Use 20 μl of tri-n-octylamine to promote the ordering of the quantum wells. Wait for 1 minute to form a dense and ordered cadmium selenide quantum well film, which is then ready for transfer to the substrate.
[0047] A method for preparing an electroluminescent diode comprises the following steps:
[0048] 5 mg / ml poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was spin-coated on a transparent conductive substrate to form a hole injection layer, and annealed at 80 degrees Celsius for 15 minutes. Subsequently, 6 mg / ml poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)] was spin-coated on the hole injection layer to form a hole transport layer, and annealed at 100 degrees Celsius for 15 minutes. The cadmium selenide quantum well film was transferred to the hole transport layer to form an ordered quantum well light-emitting layer, and annealed at 30 degrees Celsius for 15 minutes. 30 mg / ml magnesium-doped zinc oxide electron transport material was spin-coated on the ordered quantum well light-emitting layer, and annealed at 60 degrees Celsius for 15 minutes to obtain an electron transport layer. A silver metal cathode with a thickness of 70 nanometers was deposited on the electron transport layer by vacuum thermal evaporation.
[0049] Example 2
[0050] The preparation of the dense and ordered cadmium selenide quantum well film is the same as that in Example 1.
[0051] A method for preparing an electroluminescent diode comprises the following steps:
[0052] 5 mg / ml poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was spin-coated on a transparent conductive substrate to form a hole injection layer, and annealed at 100 degrees Celsius for 15 minutes. Subsequently, 8 mg / ml poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)] was spin-coated on the hole injection layer to form a hole transport layer, and annealed at 120 degrees Celsius for 15 minutes. A dense and ordered cadmium selenide quantum well film was transferred to the hole transport layer to form an ordered quantum well light-emitting layer, and annealed at 40 degrees Celsius for 15 minutes. 30 mg / ml magnesium-doped zinc oxide electron transport material was spin-coated on the ordered quantum well light-emitting layer, and annealed at 60 degrees Celsius for 15 minutes to obtain an electron transport layer. A silver metal cathode with a thickness of 70 nm was deposited on the electron transport layer by vacuum thermal evaporation.
[0053] Example 3
[0054] The preparation of the dense and ordered cadmium selenide quantum well film is the same as in Example 1.
[0055] A method for preparing an electroluminescent diode comprises the following steps:
[0056] 5 mg / ml poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was spin-coated on a transparent conductive substrate to form a hole injection layer, which was annealed at 120 degrees Celsius for 15 minutes. Subsequently, 10 mg / ml poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)] was spin-coated on the hole injection layer to form a hole transport layer, which was annealed at 130 degrees Celsius for 15 minutes. A dense and ordered cadmium selenide quantum well film was transferred to the hole transport layer to form an ordered quantum well light-emitting layer, which was annealed at 50 degrees Celsius for 15 minutes. 30 mg / ml magnesium-doped zinc oxide electron transport material was spin-coated on the ordered quantum well light-emitting layer, and annealed at 60 degrees Celsius for 15 minutes to obtain an electron transport layer. A silver metal cathode with a thickness of 70 nm was deposited on the electron transport layer by vacuum thermal evaporation.
[0057] Example 4
[0058] The preparation of the dense and ordered cadmium selenide quantum well film is the same as in Example 1.
[0059] A method for preparing an electroluminescent diode comprises the following steps:
[0060] 5 mg / ml poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was spin-coated on a transparent conductive substrate to form a hole injection layer, which was annealed at 140 degrees Celsius for 15 minutes. Subsequently, 12 mg / ml poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)] was spin-coated on the hole injection layer to form a hole transport layer, which was annealed at 140 degrees Celsius for 15 minutes. A dense and ordered cadmium selenide quantum well film was transferred to the hole transport layer to form an ordered quantum well light-emitting layer, which was annealed at 60 degrees Celsius for 15 minutes. 30 mg / ml magnesium-doped zinc oxide electron transport material was spin-coated on the ordered quantum well light-emitting layer, and annealed at 60 degrees Celsius for 15 minutes to obtain an electron transport layer. A silver metal cathode with a thickness of 70 nm was deposited on the electron transport layer by vacuum thermal evaporation.
[0061] Example 5
[0062] The preparation of the dense and ordered cadmium selenide quantum well film is the same as that in Example 1.
[0063] A method for preparing an electroluminescent diode comprises the following steps:
[0064] 5 mg / ml poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was spin-coated on a transparent conductive substrate to form a hole injection layer, which was annealed at 150 degrees Celsius for 15 minutes. Subsequently, 14 mg / ml poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)] was spin-coated on the hole injection layer to form a hole transport layer, which was annealed at 150 degrees Celsius for 15 minutes. A dense and ordered cadmium selenide quantum well film was transferred to the hole transport layer to form an ordered quantum well light-emitting layer, which was annealed at 70 degrees Celsius for 15 minutes. 30 mg / ml magnesium-doped zinc oxide electron transport material was spin-coated on the ordered quantum well light-emitting layer, and annealed at 60 degrees Celsius for 15 minutes to obtain an electron transport layer. A silver metal cathode with a thickness of 70 nm was deposited on the electron transport layer by vacuum thermal evaporation.
[0065] Table 1 Quantum well and its electroluminescent LED performance
[0066]
[0067] It can be seen from the above table that with the increase of the hole transport layer concentration and the increase of annealing temperature, the efficiency of the device increases and then decreases. The device with a hole transport layer concentration of 10 mg / mL and annealed at 140 degrees Celsius has the highest efficiency, reaching 19%.
[0068] Example 6
[0069] The method for preparing a dense and ordered cadmium selenide quantum well film in Example 1 is adopted, except that step (4) is performed as follows:
[0070] (4) Prepare a 20 mg / ml colloidal cadmium selenide quantum well chloroform solution. In a nitrogen-protected environment at an ambient temperature of 20 degrees Celsius, drop 20 μl of the quantum well solution on 20 ml of ethylene glycol solution. Use 100 μl of tri-n-octylamine to promote the ordering of the quantum wells. Wait for 3 minutes to form a dense and ordered cadmium selenide quantum well film, which is then ready for transfer to the substrate.
[0071] A method for preparing an electroluminescent diode comprises the following steps:
[0072] 5 mg / ml poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was spin-coated on a transparent conductive substrate to form a hole injection layer, which was annealed at 80 degrees Celsius for 15 minutes. Subsequently, 6 mg / ml poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)] was spin-coated on the hole injection layer to form a hole transport layer, which was annealed at 100 degrees Celsius for 15 minutes. A dense and ordered cadmium selenide quantum well film was transferred to the hole transport layer to form an ordered quantum well light-emitting layer, which was annealed at 30 degrees Celsius for 15 minutes. 30 mg / ml magnesium-doped zinc oxide electron transport material was spin-coated on the ordered quantum well light-emitting layer, and annealed at 60 degrees Celsius for 15 minutes to obtain an electron transport layer. A silver metal cathode with a thickness of 70 nm was deposited on the electron transport layer by vacuum thermal evaporation.
[0073] Example 7
[0074] The preparation of the dense and ordered cadmium selenide quantum well film is the same as that in Example 6.
[0075] A method for preparing an electroluminescent diode comprises the following steps:
[0076] 5 mg / ml poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was spin-coated on a transparent conductive substrate to form a hole injection layer, and annealed at 100 degrees Celsius for 15 minutes. Subsequently, 8 mg / ml poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)] was spin-coated on the hole injection layer to form a hole transport layer, and annealed at 120 degrees Celsius for 15 minutes. A dense and ordered cadmium selenide quantum well film was transferred to the hole transport layer to form an ordered quantum well light-emitting layer, and annealed at 30 degrees Celsius for 15 minutes. 30 mg / ml magnesium-doped zinc oxide electron transport material was spin-coated on the ordered quantum well light-emitting layer, and annealed at 60 degrees Celsius for 15 minutes to obtain an electron transport layer. A silver metal cathode with a thickness of 70 nm was deposited on the electron transport layer by vacuum thermal evaporation.
[0077] Example 8
[0078] The preparation of the dense and ordered cadmium selenide quantum well film is the same as that in Example 6.
[0079] A method for preparing an electroluminescent diode comprises the following steps:
[0080] 5 mg / ml poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was spin-coated on a transparent conductive substrate to form a hole injection layer, which was annealed at 120 degrees Celsius for 15 minutes. Subsequently, 6 mg / ml poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)] was spin-coated on the hole injection layer to form a hole transport layer, which was annealed at 130 degrees Celsius for 15 minutes. A dense and ordered cadmium selenide quantum well film was transferred to the hole transport layer to form an ordered quantum well light-emitting layer, which was annealed at 30 degrees Celsius for 15 minutes. 30 mg / ml magnesium-doped zinc oxide electron transport material was spin-coated on the ordered quantum well light-emitting layer, and annealed at 60 degrees Celsius for 15 minutes to obtain an electron transport layer. A silver metal cathode with a thickness of 70 nm was deposited on the electron transport layer by vacuum thermal evaporation.
[0081] Example 9
[0082] The preparation of the dense and ordered cadmium selenide quantum well film is the same as that in Example 6.
[0083] A method for preparing an electroluminescent diode comprises the following steps:
[0084] 5 mg / ml poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was spin-coated on a transparent conductive substrate to form a hole injection layer, which was annealed at 140 degrees Celsius for 15 minutes. Subsequently, 6 mg / ml poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)] was spin-coated on the hole injection layer to form a hole transport layer, which was annealed at 140 degrees Celsius for 15 minutes. A dense and ordered cadmium selenide quantum well film was transferred to the hole transport layer to form an ordered quantum well light-emitting layer, which was annealed at 30 degrees Celsius for 15 minutes. 30 mg / ml magnesium-doped zinc oxide electron transport material was spin-coated on the ordered quantum well light-emitting layer, and annealed at 60 degrees Celsius for 15 minutes to obtain an electron transport layer. A silver metal cathode with a thickness of 70 nm was deposited on the electron transport layer by vacuum thermal evaporation.
[0085] Example 10
[0086] The preparation of the dense and ordered cadmium selenide quantum well film is the same as that in Example 6.
[0087] A method for preparing an electroluminescent diode comprises the following steps:
[0088] 5 mg / ml poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was spin-coated on a transparent conductive substrate to form a hole injection layer, which was annealed at 150 degrees Celsius for 15 minutes. Subsequently, 6 mg / ml poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)] was spin-coated on the hole injection layer to form a hole transport layer, which was annealed at 150 degrees Celsius for 15 minutes. A dense and ordered cadmium selenide quantum well film was transferred to the hole transport layer to form an ordered quantum well light-emitting layer, which was annealed at 30 degrees Celsius for 15 minutes. 30 mg / ml magnesium-doped zinc oxide electron transport material was spin-coated on the ordered quantum well light-emitting layer, and annealed at 60 degrees Celsius for 15 minutes to obtain an electron transport layer. A silver metal cathode with a thickness of 70 nm was deposited on the electron transport layer by vacuum thermal evaporation.
[0089] Table 2 Quantum well and its electroluminescent LED performance
[0090]
[0091] As can be seen from the table above, increasing the concentration of the quantum well solution to 20 mg / ml and increasing the injection amount of tri-n-octylamine can produce a more ordered and compact quantum well film for device preparation. At the same time, it can be concluded from Examples 6-10 that with the increase in the concentration of the hole transport layer and the increase in the annealing temperature of the hole transport layer, the performance of the device first increases and then decreases. Under the conditions of Example 7, a high external quantum efficiency of 25% is achieved.
[0092] Embodiment 11
[0093] The method for preparing a dense and ordered cadmium selenide quantum well film in Example 1 is adopted, except that step (4) is performed as follows:
[0094] (4) Prepare a chloroform solution of colloidal cadmium selenide quantum wells with a concentration of 50 mg / ml. In a nitrogen-protected environment at an ambient temperature of 30 degrees Celsius, drop 30 μl of the quantum well solution on 20 ml of ethylene glycol solution. Use 200 μl of tri-n-octylamine to promote the orderly arrangement of the quantum wells. Wait for 5 minutes to form a dense and ordered cadmium selenide quantum well film, which is then ready for transfer to the substrate.
[0095] 5 mg / ml poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was spin-coated on a transparent conductive substrate to form a hole injection layer, which was annealed at 80 degrees Celsius for 15 minutes. Subsequently, 6 mg / ml poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)] was spin-coated on the hole injection layer to form a hole transport layer, which was annealed at 100 degrees Celsius for 15 minutes. A dense and ordered cadmium selenide quantum well film was transferred to the hole transport layer to form an ordered quantum well light-emitting layer, which was annealed at 30 degrees Celsius for 15 minutes. 30 mg / ml magnesium-doped zinc oxide electron transport material was spin-coated on the ordered quantum well light-emitting layer, and annealed at 60 degrees Celsius for 15 minutes to obtain an electron transport layer. A silver metal cathode with a thickness of 70 nm was deposited on the electron transport layer by vacuum thermal evaporation.
[0096] Example 12
[0097] The preparation of dense and ordered cadmium selenide quantum well film is the same as Example 11.
[0098] A method for preparing an electroluminescent diode comprises the following steps:
[0099] 5 mg / ml poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was spin-coated on a transparent conductive substrate to form a hole injection layer, and annealed at 100 degrees Celsius for 15 minutes. Subsequently, 8 mg / ml poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)] was spin-coated on the hole injection layer to form a hole transport layer, and annealed at 120 degrees Celsius for 15 minutes. A dense and ordered cadmium selenide quantum well film was transferred to the hole transport layer to form an ordered quantum well light-emitting layer, and annealed at 30 degrees Celsius for 15 minutes. 30 mg / ml magnesium-doped zinc oxide electron transport material was spin-coated on the ordered quantum well light-emitting layer, and annealed at 60 degrees Celsius for 15 minutes to obtain an electron transport layer. A silver metal cathode with a thickness of 70 nm was deposited on the electron transport layer by vacuum thermal evaporation.
[0100] Embodiment 13
[0101] The preparation of dense and ordered cadmium selenide quantum well film is the same as Example 11.
[0102] A method for preparing an electroluminescent diode comprises the following steps:
[0103] 5 mg / ml poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was spin-coated on a transparent conductive substrate to form a hole injection layer, which was annealed at 120 degrees Celsius for 15 minutes. Subsequently, 10 mg / ml poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)] was spin-coated on the hole injection layer to form a hole transport layer, which was annealed at 140 degrees Celsius for 15 minutes. A dense and ordered cadmium selenide quantum well film was transferred to the hole transport layer to form an ordered quantum well light-emitting layer, which was annealed at 30 degrees Celsius for 15 minutes. 30 mg / ml magnesium-doped zinc oxide electron transport material was spin-coated on the ordered quantum well light-emitting layer, and annealed at 60 degrees Celsius for 15 minutes to obtain an electron transport layer. A silver metal cathode with a thickness of 70 nm was deposited on the electron transport layer by vacuum thermal evaporation.
[0104] Table 3 Quantum well and its electroluminescent LED performance
[0105]
[0106] As can be seen from the table above, the concentration of the quantum well solution is further increased to 20 mg / ml, the injection amount of tri-n-octylamine is increased again, and the quantum well film is prepared to prepare the device. It can be concluded from Examples 11-13 that the performance of the device first increases and then decreases with the increase of the concentration of the hole transport layer and the increase of the annealing temperature of the hole transport layer. Under the conditions of Example 12, an external quantum efficiency of 19% is achieved. The efficiency of Examples 11-13 is lower than that of Examples 6-10, indicating that the concentration of the quantum well solution is too high and the injection amount of tri-n-octylamine is too much.
[0107] In order to demonstrate the universality of the ordered and dense quantum well light-emitting diode of the present invention, this embodiment uses red, green and blue quantum wells to prepare light-emitting diodes. The preparation process refers to Example 7. The results show that the external quantum efficiency of the ordered and dense red, green and blue quantum well light-emitting diodes is higher than 20% of the external quantum efficiency.
[0108] Table 4 Performance of quantum well and its electroluminescent LED
[0109]
[0110] Although several embodiments of the present invention have been given herein, those skilled in the art should understand that the embodiments of the present invention may be modified without departing from the spirit of the present invention. The above embodiments are merely exemplary and should not be used as a limitation on the scope of the present invention.
Claims
1. A method for preparing a dense and ordered cadmium selenide quantum well film, characterized in that: The following steps are involved: (1) dissolving sodium myristate and cadmium nitrate tetrahydrate in a first solvent respectively, mixing them after they are completely dissolved to form cadmium myristate, filtering, washing with the first solvent, and drying for later use; (2) Cadmium selenide quantum well core: 0.2-1.6 mmol of cadmium tetradecanoate, 0.1-0.8 mmol of selenium powder and solvent are mixed, heated to 140-200 degrees Celsius in an inert gas atmosphere, cadmium acetate dihydrate is injected, and then heated to 200-260 degrees Celsius and kept warm for 5-20 minutes, 0.2-1 ml of oleic acid is injected, cooled, and the quantum well is washed with a mixed solution of n-hexane and ethanol, and redispersed with a second solvent to form a cadmium selenide quantum well core solution; (3) Core-shell structure cadmium selenide / cadmium zinc sulfur quantum well: add 0.1-0.3 mmol anhydrous cadmium acetate, 0.3-0.9 mmol anhydrous zinc acetate, 0.5-1.5 ml oleic acid, and 0.2-1 ml 1-octadecene to the core solution of cadmium selenide quantum well, and heat to 70-100 degrees Celsius in an inert gas atmosphere, keep warm for 0.2-1 hour, inject 0.2-1 ml oleylamine, and heat to 280-320 degrees Celsius. When the temperature reaches 120-180 degrees Celsius, start injecting octanethiol, keep warm at 280-320 degrees Celsius for 0.5-1.5 hours, and cool to obtain core-shell structure cadmium selenide / cadmium zinc sulfur quantum well; (4) washing the core-shell structured cadmium selenide / cadmium zinc sulfur quantum wells with a mixed solution of a second solvent and a first solvent; and redispersing the solution with a second solvent to form a core-shell structured cadmium selenide / cadmium zinc sulfur quantum well solution having a concentration of 10 to 50 mg / ml; (5) Under nitrogen protection, at 10-30 degrees Celsius, add the core-shell structure cadmium selenide / cadmium zinc sulfur quantum well solution dropwise into the ethylene glycol solution until the multi-quantum wells cover the ethylene glycol liquid surface, and then add tri-n-octylamine at a volume ratio of 1% to 10% of the ethylene glycol solution; (6) After standing for 1 to 15 minutes, a dense and ordered cadmium selenide quantum well film is obtained.
2. The method for preparing a dense and ordered cadmium selenide quantum well film according to claim 1, characterized in that: The first solvent is methanol or ethanol, and the second solvent is n-octane, n-hexane or chloroform.
3. A dense and ordered cadmium selenide quantum well film, characterized in that: The film is prepared by the preparation method described in claim 1 or 2.
4. An electroluminescent diode, characterized in that: The light-emitting layer of the diode comprises the dense and ordered cadmium selenide quantum well film as claimed in claim 3.
5. The method for preparing an electroluminescent diode according to claim 4, characterized in that: The preparation steps are as follows: (1) A hole injection material is printed on a transparent conductive substrate to form a hole injection layer, which is then annealed at 80 to 140 degrees Celsius for 10 to 30 minutes; a hole transport material is then printed on the hole injection layer to form a hole transport layer, which is then annealed at 100 to 150 degrees Celsius for 10 to 30 minutes; (2) A dense and ordered cadmium selenide quantum well film is prepared by the preparation method described in claim 1 or 2 and transferred to the hole transport layer to form an ordered quantum well light-emitting layer, and annealed at 40 to 90 degrees Celsius for 10 to 30 minutes; (3) Spin-coat a 20-50 mg / ml zinc oxide or magnesium-doped zinc oxide ethanol solution on the quantum well light-emitting layer to form an electron transport layer, and anneal at 60-90 degrees Celsius for 10-30 minutes; (4) The metal cathode material is deposited on the electron transport layer by vacuum evaporation to form an electrode to obtain an electroluminescent diode.
6. The method for preparing an electroluminescent diode according to claim 5, characterized in that: The hole injection material is poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid); the hole transport layer material is poly[(N,N'-(4-n-butylphenyl)-N,N'-diphenyl-1,4-phenylenediamine)-ALT-(9,9-di-n-octylfluorenyl-2,7-diyl)]; the transparent conductive substrate is indium-doped tin oxide; and the metal cathode material is aluminum.
7. The method for preparing an electroluminescent diode according to claim 5, characterized in that: The thickness of the hole injection layer is 30-70 nanometers, the thickness of the hole transport layer is 30-70 nanometers, the thickness of the quantum well light-emitting layer is 5-20 nanometers, the thickness of the electron transport layer is 30-60 nanometers, and the thickness of the electrode is 70-100 nanometers.
Citation Information
Patent Citations
Preparation method of light-emitting diode, light-emitting diode and display device
CN117222283A
Preparation method of light-emitting device, light-emitting device and electronic equipment comprising light-emitting device
CN118591230A
Light-emitting devices and displays with improved performance
US20090278141A1
Light-emitting diode device, manufacturing method thereof, and display device based thereon
WO2018035948A1
Quantum dot light-emitting diode and preparation method therefor
WO2022016820A1